2018
DOI: 10.1103/physrevb.98.024308
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interfaces on the phonon density of states of nanoscale metallic multilayers: Phonon confinement and localization

Abstract: Isotope-selective 57 Fe nuclear resonant inelastic x-ray scattering (NRIXS) measurements and atomic-layer resolved density functional theory (DFT) calculations were used to investigate the effect of interfaces on the vibrational (phonon) density of states (VDOS) of (001)-oriented nanoscale Fe/Ag and Fe/Cr multilayers. The multilayers in the experiment contained isotopically enriched 57 Fe monolayers as probe layers located either at the Fe/Ag or Fe/Cr interfaces or in the center of the Fe films. This allows pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 75 publications
3
11
0
Order By: Relevance
“…We like to mention that a qualitatively similar reduction and energy shift of the LA phonon peak combined with an enhancement of the low-energy VDOS part have been observed previously by layer selective 57 Fe NRIXS combined with layer-and element-selective DFT-based calculations for Fe/Ag multilayers 45 and were interpreted in terms of high-energy phonon confinement in the Fe layers and phonon localization at the Fe/Ag interfaces, occuring as the result of the large energy mismatch between Ag and Fe LA phonons. For the energetically high Fe LA phonons (at 35.5 meV) there is no counterpart in the g(E) of the phononically soft Ag metal, because the upper phonon cutoff energy of Ag is located at only ∼ 21 meV, much lower than that of bcc Fe (∼40 meV).…”
Section: Nuclear Resonant Inelastic X-ray Scatteringsupporting
confidence: 83%
See 2 more Smart Citations
“…We like to mention that a qualitatively similar reduction and energy shift of the LA phonon peak combined with an enhancement of the low-energy VDOS part have been observed previously by layer selective 57 Fe NRIXS combined with layer-and element-selective DFT-based calculations for Fe/Ag multilayers 45 and were interpreted in terms of high-energy phonon confinement in the Fe layers and phonon localization at the Fe/Ag interfaces, occuring as the result of the large energy mismatch between Ag and Fe LA phonons. For the energetically high Fe LA phonons (at 35.5 meV) there is no counterpart in the g(E) of the phononically soft Ag metal, because the upper phonon cutoff energy of Ag is located at only ∼ 21 meV, much lower than that of bcc Fe (∼40 meV).…”
Section: Nuclear Resonant Inelastic X-ray Scatteringsupporting
confidence: 83%
“…As it has been outlined in Ref. 45 and 47, the modifications of g(E) in nanoscale multilayers are anticipated to influence the phonon transport and the vibrational thermodynamic properties in these systems. Therefore, 57 Fe NRIXS measurements and DFT-based computations of the phononic properties of [Fe/MgO] multilayers are highly desirable, in particular in view of the fact that Fe/MgO is of interest as a prototype system for the study of time-resolved phenomena on the femtosecond scale 47,48 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Combined experimental and theoretical studies of strainfree metal/semiconductor heterostructures 42 and metallic multilayers 43 demonstrated that the force constants of the atoms located at the interface are drastically reduced compared to the bulk values. This gives rise to an entirely different PDOS of the interface layers from that of a bulk material.…”
Section: Methodsmentioning
confidence: 99%
“…For all interfaces, the PRL and the DMM overestimate the thermal interface conductance. These models, however, do not account for scattering mechanisms from defects at the interface, changes in the interatomic bonds near the interface or interfacial disorder (especially in well-matched materials) [44], that results in a reduction of the thermal conductance [43].…”
Section: Thermal Interface Conductancementioning
confidence: 99%